2016
DOI: 10.1159/000443367
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Prognostic Score Predicts Response to Chemotherapy in Patients with Metastatic Breast Cancer

Abstract: Purpose: Breast cancer is one of the most common causes of cancer death in women worldwide. The Glasgow Prognostic Score (GPS), a cumulative prognostic score based on C-reactive protein and albumin, indicates the presence of a systemic inflammatory response. The GPS has been adopted as a powerful prognostic tool for patients with various types of malignant tumors, including breast cancer. The aim of this study was to assess the value of the GPS in predicting the response and toxicity in breast cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Another paper reported that patients with higher albumin level had a 45% reduced risk of death (HR, 0.55; 95% CI, 0.40–0.75; p <0.001) compared to those with lower albumin levels [ 23 ]. Other papers have reported the prognostic usefulness of a combination of serum albumin with other markers such as nutritional index (serum albumin with lymphocyte count) [ 24 ], Glasgow prognostic score (serum albumin with C-reactive protein) [ 18 ], and albumin to globulin ratio (serum albumin with globulin) [ 25 ] in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another paper reported that patients with higher albumin level had a 45% reduced risk of death (HR, 0.55; 95% CI, 0.40–0.75; p <0.001) compared to those with lower albumin levels [ 23 ]. Other papers have reported the prognostic usefulness of a combination of serum albumin with other markers such as nutritional index (serum albumin with lymphocyte count) [ 24 ], Glasgow prognostic score (serum albumin with C-reactive protein) [ 18 ], and albumin to globulin ratio (serum albumin with globulin) [ 25 ] in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, systemic inflammatory markers have also been reported to have a prognostic association with breast cancer. Most of these studies reported the prognostic roles of the neutrophil to lymphocyte ratio [ 16 ], platelet to lymphocyte ratio [ 17 ], or the Glasgow prognostic score [ 18 ] in breast cancer. Little information has been unveiled about the prognostic roles of fibrinogen [ 19 ] or albumin [ 20 ] as single markers or in combination for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although a series of studies have been carried out with regard to various therapies for BC patients, prognosis of some patients still remains poor, and the mortality rate is relatively high, due to tumor metastasis. [3][4][5] Therefore, investigation of the potential mechanism of migration and invasion of BC and exploring corresponding medical interventions is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 20-30% of all breast cancer patients who are treated with curative intent develop metastatic disease, and the 5-year OS rate for breast cancer patients with metastatic disease remains low, at approximately 2.0% [12]. Breast cancer is a heterogeneous disease, as reflected by the clinical patterns of the development of distant metastases [13,14]. Although the treatment for MBC is complex and includes a variety of options, chemotherapy remains the core MBC therapy, especially in patients with lung or liver metastases, and in patients with triple-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%